Moderate-to-vigorous physical activity among postmenopausal women: Discrepancies in accelerometry-based cut-points - Diniz, Tiego A. [UNESP]; Rossi, Fabricio E. [UNESP]; Da Costa Rosa, Clara Suemi [UNESP]; Mota, Jorge; Freitas, Ismael F. [UNESP] (Human Kinetics, 2017)
The objective of this study was to compare moderate-to-vigorous physical activity (MVPA), minutes per week (min/wk), and fulfillment of the current recommendation (150 min/wk of MVPA) based on different cut-points in postmenopausal women. The sample was composed of 233 postmenopausal women aged 59.8 ± 6.7 years old. MVPA was measured using triaxial accelerometers. Accelerometers were initialized to collect in 60-s epochs. Participants were included if using at least 5 days. MVPA min/wk were obtained using Freedson, Troiano, Copeland, and Sasaki cut-points. Box-plot indicated large mean differences between almost all cut-points, except for Freedson and Troiano (9.3 [95% LoA: -5.6; 24.3] min/wk). The proportion of women who achieved 150 min/wk of MVPA was similar between Freedson and Troiano (31% vs. 30%). Sasaki and Copeland cut-points resulted in a greater proportion than other cut-points. We concluded that the cut-points analyzed generated different results in MVPA min/wk and low agreement when using current guidelines for MVPA pattern classification, except for the comparisons between Freedson and Troiano cut-points.
Keywords: Cut-off points; Elderly; Menopause; MVPA